Sulfate-dependent anaerobic oxidation of methane at a highly dynamic bubbling site in the Eastern Sea of Marmara (Çinarcik Basin). (July 2018) - Teichert, B.M.A.; Chevalier, N.; Gussone, N.; Bayon, G.; Ponzevera, E.; Ruffine, L.; Strauss, H.
Abstract: During the MARSITECruise expedition in November 2014 on board the RV Pourquoi Pas?, multidisciplinary sampling was carried out with the ROV Victor 6000 in order to investigate biogeochemical processes taking place at cold seep environments in the Sea of Marmara. Pore water, bottom water, sediment and authigenic carbonate samples were collected from two short push cores (MRS-DV5-PC04 − 8 cm, MRS-DV5-PC01 − 12.5 cm) at an active methane bubbling site in the southeastern part of the Çinarcik Basin. Sulfate sulfur and oxygen isotope data as well as sulfide isotope data indicate that sulfate-dependent anaerobic oxidation of methane is the dominant process in the sediments. This is confirmed by archaeal lipids diagnostic for anaerobic methane oxidizers detected with strong 13 C-depletions. The available data even allows to distinguish the dominant AOM assemblages. Specific lipid patterns are consistent with a dominance of ANME-2 archaea within the microbial community. Abundant authigenic carbonates (mostly aragonite), found at all depths, show a narrow range in δ 13 C values between −27.69‰ and −33.40‰. The carbon isotopic composition of the dissolved inorganic carbon as well as strontium and calcium isotopes confirm that the current reaction zone (sulfate-methane transition zone) starts at the bottom of the core. All shallower carbonates are witnesses of paleo seepage activity. U-Th dating of four pure aragonite samples show the short time span that is preserved in core MRS-DV5-PC01 (235 ± 60 yr B.P.). Two major earthquakes of 1766 CE and 1754 CE in the Çinarcik Basin might potentially have triggered the increased seepage of methane at this location.